STUDY OF SEPARATION OF THORIUM FROM IRON AND RARE EARTH ELEMENTS IN NITRIC ACID SOLUTION BY SOLVENT EXTRACTION USING TRIBUTYL PHOSPHATE - MARDIYAH (NIM : 12513034), SYAKILA
Demand for electrical power will continue to increase along with the increase of industries and population in Indonesia. Additional alternative energy is necessary to fulfil the domestic energy demand. One of the solutions to fulfil the demand is developing nuclear power plant with a thorium-based fuel (PLTT). It is known that 90% of thorium fuel will react to generate electricity in comparison with uranium which is only 3-5%. This will give positive impact in less amount of radioactive waste generated. Thorium is found in monasit mineral, thorite (ThSiO4) and thorianit. The thorium found in Mamuju is found in many thorite minerals. In order to become a nuclear fuel, thorium must have a high purity (> 87.42%). Therefore, it is necessary to purify Th from impurities such as REEs and Fe. In this research, separation of Th from Fe and REE by solvent extraction using Tributyl Phosphate (TBP) was studied. The experiment began with digestion process of thorium ore from Mamuju, West Sulawesi. The digestion was performed using 95% H2SO4 for 1 hour, at temperature of 160Ã‚Â°C and ratio of liquid/solid of 1/2. Furthermore, the precipitation of solution from digestion process was conducted by using 25% NH4OH at pH 4.5. Precipitate of the process was re-dissolved in nitric acid and used as aqueous solution feed for solvent extraction experiments. Experimental results showed that that aqueous solution contains thorium, iron, and rare earth element with concentrations of 2.98 gpl, 6.46 gpl, and 0.34 gpl. A series of solvent extraction experiments was conducted under variations of concentration of nitric acid, extraction time, extractant concentration and O/A ratio. The best condition of the extraction process was obtained at 60Ã‚Â°C, HNO3 7M, 35% TBP and O/A ratio 2:1 for 5 minutes which resulted in 86.75% extraction of thorium, 54.28% co-extraction of Fe, and 89.90% co-extraction of REEs. Optimum scrubbing process was found at 60Ã‚Â°C, HNO3 6M concentration, O/ A ratio 2:1 for 25 minutes, to get 3.31% scrubbing of Th and 1.92% scrubbing of REEs. The best stripping condition was obtained at 60Ã‚Â°C, HNO3 0.1M, O/A ratio 2/3 for 25 minutes that resulted in 55.83% stripping of Th, 0.98% co-stripping of iron, and 1.28 % co-stripping of REEs with separation factor of βTh-Fe 128.08 and βTh-LTJ 97.29. Based on the McCabe-Thiele diagram construction, three extraction steps are required to obtain a percentage of thorium extraction> 99% at O/A ratio of 2/1, HNO3 7M and 30% TBP in 25 minutes.